The Relationship of Infant Attachment to the Incidence of Nipple Fissure in Breastfeeding: A Systematic Review - Dewi Asmaul Husna (International Journal Of Health Science, 2025)
This study emphasizes that breast milk is the most optimal source of nutrition for infants during the first six months of life, and the success of exclusive breastfeeding is influenced by several key factors, one of which is the proper attachment of the baby’s mouth during feeding. Correct attachment is crucial to ensure effective milk transfer and comfort for both mother and baby, while also preventing potential issues such as nipple abrasions or blisters that often arise from improper latching. To investigate this issue, the research was conducted using a systematic review method by identifying and analyzing relevant literature. The article search was carried out through several major databases, including Google Scholar, PubMed, and ScienceDirect, with keywords focusing on the relationship between attachment and nipple fissures, as well as attachment and cracked nipples. The initial search yielded 5,350 articles published between 2020 and 2024; however, after applying the inclusion criteria, only 15 articles were deemed relevant to the research objective. A further critical appraisal process was then conducted, resulting in 11 high-quality articles being included in the final analysis. The findings from these studies consistently highlight that poor attachment of the baby’s mouth is significantly associated with the occurrence of nipple injuries among breastfeeding mothers. Consequently, ensuring proper latching techniques can reduce the risk of nipple trauma, support maternal comfort, and improve the overall success of exclusive breastfeeding practices, which are vital for infant growth and maternal health.